The Influence of Husband’s Support on Maternal Anxiety Who Received Misoprostol Labor Induction At Merauke Regional Hospital - Lena Berlenda Rumadas; Candra Wahyuni; Anggrawati Wulandari; Shanty Natalia (Journal of Health Science Community, 2024)
Childbirth is a process of expelling viable products of conception (fetus and urine) out of the uterus through the birth canal or other means. Induction of labor causes the mother to experience discomfort in the form of labor pain. Anxiety is one of the main factors that influences the course of labor and results in a long opening. The husband’s role is a very important factor in the labor process, because the husband can foster feelings of self-confidence and form a healthy mentality, so that feelings of anxiety and fear disappear. This research uses an observational analytical research design with a cross sectional approach. Using the accidental sampling technique, a sample of 35 respondents was obtained, from 142 populations, in December at the Merauke District Hospital, the independent variables were husband’s support and Misoprostol labor induction using a questionnaire and the dependent variable was maternal anxiety during childbirth using observation. The Chi-Square statistical test was used to determine the relationship between the three variables. The results of the study showed that the total number of respondents was 35 mothers who received Misoprostol labor induction, the majority (most) received support from their husbands, namely 19 respondents (54.3%) and the most respondents experienced moderate levels of anxiety, namely 16 respondents (45.7 %), and it can be seen that the most common type of misoprostol labor induction administered vaginally to mothers giving birth was 21 respondents (60%). Analysis using the Chi-Square statistical test resulted in p = 0.012 < 0.05, so H0 was rejected and H1 was accepted, which means it can be concluded that there is an influence of husband’s support on the anxiety of mothers who receive misoprostol labor induction at the Merauke District Hospital. In this context, the husband’s role as companion and supporter has a significant impact on the level of anxiety of mothers giving birth. First of all, the husband’s presence during the labor induction process.